Adenoid cystic carcinoma of the parotid gland: Anastamosis of the facial nerve with the great auricular nerve after radical parotidectomy - Bahadir Osman; Livaoglu Murat; Ural Ahmet (Indian Journal of Plastic Surgery)
Adenoid cystic carcinoma of the parotid gland is a rare and slowly growing, but highly malignant tumor. Surgical resection of a malignant parotid tumor should include resection of the facial nerve when the nerve is involved in the tumor. Facial nerve reconstruction is required after nerve resection. A 14 year-old female presented with complaints of painless enlargement of the right parotid gland and facial asymmetry. Physical examination revealed a firm mass in the region of the parotid gland as well as right facial paralysis. Biopsy obtained from the mass showed an adenoid cystic carcinoma of the parotid gland. A radical parotidectomy with a modified radical neck dissection was carried out. Grafting material for the facial reconstruction was harvested from the great auricular nerve. The proximal main trunk and each distal branch of the facial nerve were coapted with the greater auricular nerve. The patient received radiotherapy after surgery and was seen to achieve grade IV facial function one year after surgery. Thus, the great auricular nerve is appropriate grafting material for coaptation of each distal branch of the facial nerve.